Aznar Gil, Federico R., La administration de los bienes temporales de la Iglesia, Salamanca 1993: [Rezension] - Fuentes Alonso, José Antonio (Ius canonicum, 1994)
"Die Verwaltung der zeitlichen Güter der Kirche"